Assessment of Different Conventional and Biofortified Wheat Genotypes Based on Biology and Damage Pattern of Rhyzopertha dominica and Trogoderma granarium - Hafiz Muhammad Bilal Yousuf; Muhammad Yasin; Muhammad Asif Khan; Asim Abbasi; Muhammad Arshad; Muhammad Anjum Aqueel; Inzamam Ul Haq; Waleed A. A. Alsakkaf; Marwa I. Mackled; Nazih Y. Rebouh; Hayssam M. Ali (Insects)
The lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) and khapra beetle, Trogoderma granarium E. (Coleoptera: Dermestidae) are primary stored-grain insect pests. Differences in certain biological and physical parameters of both pest species and wheat genotypes were investigated under laboratory conditions. Zinc (Zn)-biofortified (Zincol-2016 and Akbar-2019) and conventional (Arooj-2022, Nawab-2021, Dilkash-2021, Bhakkar Star-2019) wheat genotypes were used in this study. Zn-biofortified genotypes outperformed the conventional ones, with significant differences observed in fecundity, percent adult emergence, total developmental duration, percent grain damage, and weight loss of both insect species. The results further revealed that the fecundity of R. dominica and T. granarium were lowest on Akbar-2019 in both the free-choice test (42.50 and 33.17) and no-choice test (35.50 and 32.50), respectively. Similarly, percent adult emergence of both insect species was also lowest on Akbar-2019 in both the free-choice test (69.78 and 70.28%) and no-choice test (67.38 and 70.71%). The total developmental period also showed significant variation among the tested genotypes. The longest developmental period was recorded in Akbar-2019, i.e., 44.33 and 58.83 days, for R. dominica and T. granarium, respectively. Similarly, percent grain damage (13.23 and 10.33%) and weight loss (3.62 and 2.12%) were found to be minimum in Akbar-2019 for both pest species, respectively. Additionally, a positive correlation was observed between grain moisture content and damage parameters, suggesting that the higher moisture content may aggravate the percent grain damage and weight loss. These findings indicate that the nutritional qualities of Zn-biofortified wheat genotypes negatively affected the development of both insect species; thus, it can be an efficacious approach not only for ensuring food security but also for protecting grains against storage pests.